Reforming the civil service for government performance : a partnership perspective - Rahman, A. T. R. (Abu Tayeb Rafiqur), 1936- (Dhaka : University Press Ltd., 2001)
With reference to developing countries.
Includes bibliographical references (pages [156]-159) and index.
16778, 12460
Keywords: Civil service -- Developing countries; Developing countries -- Politics and government